A Copper Complex as Catalyst in Proton Reduction. Issue 28 (30th May 2017) - Nestke, Sebastian; Kügler, Merle; Scholz, Julius; Wilken, Mona; Jooss, Christian; Siewert, Inke
Abstract : Herein, we present the application of a copper(II) complex, [CuL 1 ](ClO4 )2 (L 1 : 1, 3‐bis[(1‐methyl‐1 H ‐imidazol‐2‐yl)methyl]aminopropan‐2‐ol) (1 ), as a catalyst in the electrochemically driven hydrogen evolution reaction (HER) in buffered water and standardised artificial seawater. Potentiometric titrations revealed that a [Cu II HL 1 ] 3+ species is the main species in aqueous solutions at pH 4 to 8. Complex solutions of1 are active in the electrochemical HER at solutions at pH 4 to 8, yet, the active species is different depending on the reaction medium. In acidic and neutral phosphate‐buffered water, we observed the highest catalytic activity. However, the initially formed [Cu I H2 L 1 ] 3+ species decomposes to some extent under the reductive conditions in phosphate‐buffered solutions and the high activity originates from the decomposition products (elemental copper and copper‐oxido species) and from soluble species. In artificial seawater the catalytic activity was much lower; virtually no decomposition was observed, and likely the complex represents the active species. Abstract : We present the application of a copper(II) complex, [CuL 1 ](ClO4 )2 (1 ), as a catalyst in the electrochemically driven hydrogen evolution reaction (HER) in buffered water and seawater. Homogeneous and heterogeneous proton reduction catalysis was observed depending on the reaction conditions.